Time Interaction With Two Spatial Dimensions: From Left/Right to Near/Far - Candini, Michela; D’Angelo, Mariano; Frassinetti, Francesca (Frontiers in Human Neuroscience, 2022)
In this study, we explored the time and space relationship according to two different spatial codings, namely, the left/right extension and the reachability of stimulus along a near/far dimension. Four experiments were carried out in which healthy participants performed the time and spatial bisection tasks in near/far space, before and after short or long tool-use training. Stimuli were prebisected horizontal lines of different temporal durations in which the midpoint was manipulated according to the Muller-Lyer illusion. The perceptual illusory effects emerged in spatial but not temporal judgments. We revealed that temporal and spatial representations dynamically change according to the action potentialities of an individual: temporal duration was perceived as shorter and the perceived line’s midpoint was shifted to the left in far than in near space. Crucially, this dissociation disappeared following a long but not short tool-use training. Finally, we observed age-related differences in spatial attention which may be crucial in building the memory temporal standard to categorize durations.